Testicular Nuclear Receptor 4 Regulates Proliferation and Apoptosis of Bladder Cancer via Bcl-2 - Wang, Huan; Luo, Wenqin; Wang, Xuliang; Xue, Dingwei; Ren, Liangliang; Xu, Li; Ge, Guangju; Xia, Liqun; Yu, Shicheng; Wang, Mingchao; Zhou, Zhenwei; Li, Gonghui; et al. (Frontiers in Molecular Biosciences, 2021)
Testicular nuclear receptor 4 (TR4), belonging to the nuclear hormone receptor family, acts as a ligand-activated transcription factor and functions in many biological processes such as development, cellular differentiation, and homeostasis. Recent studies showed that TR4 played an important role in prostate cancer, renal cell carcinoma and hepatocellular carcinoma, however its potential linkage to bladder cancer (BC) remained unknown. Here, we found that bladder cancer exhibited high expression of TR4 compared with the normal tissues. Overexpressing TR4 promoted the bladder cancer cells proliferation and knocking down TR4 with TR4-siRNA suppressed the bladder cancer cells proliferation. Mechanism studies revealed that TR4 functioned through altering the expression of Bcl-2 to regulate the bladder cancer cells apoptosis. In vivo, we also confirmed that TR4 knock-down mice (TR4+/-) showed slower bladder cancer growth compared with the wild-type mice (TR4+/+) induced by the carcinogenic chemicals. More importantly, TR4+/- mice showed lower grade of histopathology than the control group. In conclusion, these results indicated TR4 played a key role in bladder cancer proliferation, and targeting TR4 might be a potential strategy for bladder cancer.